1979
DOI: 10.1590/s0034-89101979000200008
|View full text |Cite
|
Sign up to set email alerts
|

Interação de fatores riscos em tuberculose

Abstract: Estudou-se o possível sinergismo dos fatores alcoolismo e tabagismo na tuberculose pulmonar, a partir de dados de um estudo caso-controle onde 854 pessoas foram entrevistadas (sendo 427 casos-pacientes portadores de tuberculose pulmonar e 427 controles) e questionadas quanto ao hábito de ingestão alcoólica e o de fumar em períodos precedendo ao diagnóstico da doença. Concluiu-se que existe pequena interação destes fatores na tuberculose pulmonar; o hábito de fumar estaria relacionado com a doença tuberculose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
3
0
1
Order By: Relevance
“…The present study found no association between alcohol consumption and TB, which differs from other studies which concluded that alcohol had a stronger association with tuberculosis [ 11 ]. Ruffino-Neto, several decades ago, investigated the role of alcohol consumption and smoking in the risk of developing tuberculosis and found that smoking was associated with tuberculosis only in the group of drinkers [ 12 , 13 ]. However, alcoholics should also be counseled effectively to wean them away from these unhealthy behaviors and minimize the risk of developing the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found no association between alcohol consumption and TB, which differs from other studies which concluded that alcohol had a stronger association with tuberculosis [ 11 ]. Ruffino-Neto, several decades ago, investigated the role of alcohol consumption and smoking in the risk of developing tuberculosis and found that smoking was associated with tuberculosis only in the group of drinkers [ 12 , 13 ]. However, alcoholics should also be counseled effectively to wean them away from these unhealthy behaviors and minimize the risk of developing the disease.…”
Section: Discussionmentioning
confidence: 99%
“…did not control for smoking, and if alcohol and tobacco consumption are associated in that setting, the association measured may be reflecting an unmeasured effect of smoking. In relation to the role of alcohol consumption and smoking in the risk of developing tuberculosis (rather than relapsing), Ruffino-Neto and Ruffino, 19 several decades ago, investigated the synergism between these two factors and found that smoking was associated with tuberculosis only in the group of drinkers (alcohol), whereas Brown and Campbell, on examining confounding between the two variables, concluded that alcohol had a stronger association with tuberculosis. 20 Due to these findings, smoking was adjusted for alcohol consumption in the present study, but there was no confounding effect between alcohol consumption and smoking on the risk of relapse (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that in the second half of the last century several studies pointed to an association between smoking and developing tuberculosis, 19 , 21 , 22 there was a gap of decades until scientific interest in this topic was renewed. More recently, studies have investigated and found evidence of smoking as a risk factor for developing tuberculosis, independently, or interacting with alcohol consumption, and evidence of progression from latent tuberculosis infection to disease.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo dados da World Health Organization -WHO (1997), um terço da população mundial está infectada pelo Mycobacterium tuberculosis. A tuberculose é a doença infecciosa que mais mata, correspondendo a 25% do total de óbitos evitáveis nos países em desenvolvimento 11 .…”
Section: Introductionunclassified